Reflections on Early Christian Topography - Greenslade, Stanley L. (Studies in church history, 1966)
One day early in the sixth century a house by the convent of nuns in the city of Arles caught fire. As the flames drew nearer, the cloistered ladies, forbidden to go outside, flung books and treasures and finally themselves into cisterns which were mercifully empty (one might think some water useful). The praepositi ran to Bishop Caesarius, warning him that the fire was getting close to his cell. Quickly he came out, went along the wall to the spot where the flames burned brightest, shouted encouragement from the wall, and brought the fire under control by his prayers.This story from the near-contemporary life of Caesarius throws an uncertain light upon the Christian topography of Arles. From the Vita and from the Rule which Caesarius gave to his nuns we know that he had brought the convent within the walls after the Franco-Burgundian siege of A.D. 508. The Rule speaks of turris juxta pomoerium, and there it is still, Tour des Mourgues, turrsi monacharum, at the south-west corner of the Roman walls. In that corner was the Abbaye de S. Césaire until the Revolution; and recently a cistern has been uncovered which may well be that in which the nuns took refuge. So far, so good. But where was the bishop? Any well-instructed schoolboy will convict me of a howler. If the praepositi told Caesarius that the fire was near cellae suae, it was their cell, not his. But few schoolboys are encouraged to read late Latin or even colloquial Latin of classical times. I shall continue to trust that they were not so pusillanimous as to leave the ladies to their fate and run trembling to the bishop in fear for their own rooms. They feared for him.